Pengembangan desain E-Bike ITSB model 2.0. untuk kendaraan patroli keamanan kawasan terpadu - Wildan Aulia; Heru Widodo (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2021)
E-Bike ITSB is a solar powered electric commuter vehicle developed by ITSB since 2016. The first E-Bike ITSB model has entered the production simulation stage which began in 2017. According to the ITSB Product Design Study Center roadmap, E-Bike ITSB must begin to enter the utility expansion stage. One of the potential needs to be met by the E-Bike ITSB is an operational vehicle for security officers in an integrated area. Design aspects that are considered are the usability & visual quality of the product, and user ergonomics/anthropometry. The design method was carried out through analitycal prototyping. Mobility studies are carried out by survey, interview and route mapping. The case study was conducted in Kota Deltamas. The design direction is obtained through perceptual mapping analysis which is used to identify the expected image on the product. The study results show that the second E-Bike ITSB model image is expected to lead to offroad-like – motorcycle-like. The specifications of the second E-Bike model cannot be the same as the first model. The e-bike must be able to go up to 80 km/hr. These requirements change the E-Bike ITSB in body frame, electrical and motor specifications.